A new recyclable functionalized mesoporous SBA-15 catalyst grafted with chiral Fe(iii) sites for the enantioselective aminolysis of racemic epoxides under solvent free conditions. Issue 100 (12th October 2016) - Halder, Mita; Bhanja, Piyali; Roy, Susmita; Ghosh, Swarbhanu; Kundu, Sudipta; Islam, Md. Mominul; Islam, Sk. Manirul
Abstract : A mesoporous SBA-15 supported chiral Fe(iii )-catalyst was prepared and used for the synthesis of chiral β-amino alcohols with very good yields and enantioselectivities (ee upto 98%) under neat conditions at RT. Abstract : An efficient and enantioselective strategy for the catalytic ring opening of racemic meso and terminal epoxides with aromatic as well as cyclic amine derivatives has been reported over a new mesoporous SBA-15 catalyst grafted with a chiral Fe(iii ) complex. The catalyst generates the expected chiral β-amino alcohols in over all better yields along with brilliant enantioselectivity (ee upto >99%) under solvent-free reaction condition at RT within 2–4 h reaction time. The catalyst is characterized in detail by PXRD, BET, HR-TEM, EPR, AAS, CHN analysis, IR and UV-Vis spectroscopic analysis etc. The catalyst is easily recoverable from the reaction system and can be used for five consecutive times without considerable loss of its catalytic activity as well as selectivity, which suggest sustainability of this chiral mesoporous catalyst.